A biopsychosocial model of resilience for multiple sclerosis. (November 2015) - Black, Rebecca; Dorstyn, Diana
The concept of resilience remains under-researched in the multiple sclerosis literature. Consequently, current understanding of the unique and joint contribution of disability-specific variables, cognitive-behavioural skills and social resources to this dynamic process is limited. A holistic model of resilience was therefore developed and tested. Results of an online survey completed by 196 adults with multiple sclerosis revealed both direct and indirect pathways to resilience, with positive affect and self-efficacy being the strongest predictors. The findings lend support to psychological interventions which focus on promoting the personal resources and assets needed to cope effectively with multiple sclerosis.